Promising images of love: a qualitative-ethnographic study about the mediatised memories of weddings [version 2; peer review: 1 approved, 4 approved with reservations] - Marie-Therese Mäder (Open Research Europe)
Background Digital and electronic media play a central role in weddings, capturing everything from the preparation to the ceremony itself and beyond. These media make specific moments of the wedding day memorable. But how do couples manage their wedding photos and videos, and what role do these media play in evoking memories of the event's religious and secular dimensions? These questions are explored within the theoretical framework of mediatisation and memory processes. This paper argues that the mediatization of weddings evokes emotions that strengthen the impact of these memories. Media shape how these events are recalled, leading to a partial homogenization of memories, where cultural and religious differences, as well as sexual orientation, become less prominent. Methods This interdisciplinary qualitative-ethnographic research is based on twenty-seven semi-structured video recorded interviews conducted in Italy, Germany, and Switzerland with homo- and heterosexual married couples from different cultural-religious backgrounds. The couples shared their wedding album or video and developed their wedding narrative by looking at the photographs and videos. Results Taking photos during the wedding becomes an important part of the ritual, independent of any cultural or religious background, gender and sexual orientation. The ceremony itself is emphasized in the photos and the videos. This homogenisation of the rite of passage equally occurs in the photographic representations of weddings and in turn influences how the wedding is remembered. The findings further confirm that heterosexual marriage representations reinforce gender stereotypes. The brides/wives of heterosexual couples are significantly more invested in the production and reception of wedding media, whereas homosexual couples participated in the conversation rather equally. Conclusions The homogenization of representation and memory becomes part of the rite of passage’s cultural-collective memory that connects the individual couples. The mediatisation of weddings strengthens the feeling of belonging to a community that transcends cultural-religious identities.